Selective migration and engraftment of bone marrow mesenchymal stem cells in rat lumbar dorsal root ganglia after sciatic nerve constriction - Coronel, Maria Florencia (2006)
Bone marrow mesenchymal stem cells (MSCs) preferentially migrate to the injured hemisphere when administered intravenously to rats with traumatic or ischemic brain injuries. In this study, we have investigated the localization of MSCs injected into the lumbar-4 dorsal root ganglion (L4-DRG) of rats with a sciatic nerve single ligature nerve constriction (SLNC). MSCs were isolated by their adherence to plastic, cultured until confluence and labelled with Hoechst. Animals with a unilateral injection of MSCs were subjected to an ipsilateral, bilateral or contralateral SLNC. After 9 days, they were perfused and the lumbar DRGs were dissected out, cut in a cryostat and observed with a fluorescence microscope. Large numbers of Hoechst-positive cells were observed in the injected L4-DRG, distributed around primary afferent neurons, resembling the anatomical localization of glial cells. In animals with an ipsilateral SLNC, some cells were detected in the ipsilateral L3, L5 or L6-DRGs but not in the contralateral ganglia. In animals with a bilateral lesion, MSCs migrated to both the ipsilateral and contralateral DRGs whereas in animals with a contralateral ligature, MSCs migrated to the contralateral DRGs. These results suggest that MSCs preferentially engraft in DRGs hosting primary sensory neurons affected by a lesion of their peripheral branches. Further studies should be carried out in order to elucidate the molecular mechanisms involved in this migration and homing, in order to evaluate the possible use of MSCs as a new therapeutic strategy for the treatment of peripheral nerve neuropathies.